Field research 2012 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Includes research reports from these locations: East Central Kansas Experiment Field, Kansas River Valley Experiment Field, and Western Kansas Agricultural Research Centers.
Keywords: Kansas; Agriculture; Crops; Disease control; Fertilizer; Irrigation; Weed control